Unvegetated corridors nonlinearly regulate hydrological connectivity and sediment delivery in a microtidal marsh - Dawei Wang; Junhong Bai; Ken Schoutens; Jingfeng Wang; Wei Wang; Chuanhui Gu (CATENA, 2026)

Meta-Analysis of the Effects of Cognitive Behavioral Therapy on Dietary Habits and Emotional Outcomes in Patients With Obesity Undergoing Metabolic and Bariatric Surgery - Haowen Gao; Guiqi Wang; Xinxin Zhang; Haobing Guo; Liyun Pang; Jingfeng Gu (Journal of Nutrition Education and Behavior, 2025)

A new pathway for anaerobic biotransformation of marine toxin domoic acid - Miaomiao Du; Yuan Jin; Jingfeng Fan; Shuaijun Zan; Chen Gu; Jing Wang (Environmental Science and Pollution Research, 2023)

Comprehensive evaluation and analysis of the salinity stress response mechanisms based on transcriptome and metabolome of Staphylococcus aureus - Ying Feng; Dizhou Gu; Ziyan Wang; Chenyang Lu; Jingfeng Fan; Jun Zhou; Rixin Wang; Xiurong Su (Archives of Microbiology, 2022)

Study on the stability of slopes on both sides of highway in rock area under rainfall - Xiangyun Luo; Jingfeng Yuan; Tiantian Gu (Arabian Journal of Geosciences, 2021)

Moisture availability mediates the relationship between terrestrial gross primary production and solar‐induced chlorophyll fluorescence: Insights from global‐scale variations - Anping Chen; Jiafu Mao; Daniel Ricciuto; Jingfeng Xiao; Christian Frankenberg; Xing Li; Peter E. Thornton; Lianhong Gu; Alan K. Knapp (Global Change Biology, 2021)
Effective use of solar‐induced chlorophyll fluorescence (SIF) to estimate and monitor gross primary production (GPP) in terrestrial ecosystems requires a comprehensive understanding and quantification of the relationship between SIF and GPP. To date, this understanding is incomplete and somewhat controversial in the literature. Here we derived the GPP/SIF ratio from multiple data sources as a diagnostic metric to explore its global‐scale patterns of spatial variation and potential climatic dependence. We found that the growing season GPP/SIF ratio varied substantially across global land surfaces, with the highest ratios consistently found in boreal regions. Spatial variation in GPP/SIF was strongly modulated by climate variables. The most striking pattern was a consistent decrease in GPP/SIF from cold‐and‐wet climates to hot‐and‐dry climates. We propose that the reduction in GPP/SIF with decreasing moisture availability may be related to stomatal responses to aridity. Furthermore, we show that GPP/SIF can be empirically modeled from climate variables using a machine learning (random forest) framework, which can improve the modeling of ecosystem production and quantify its uncertainty in global terrestrial biosphere models. Our results point to the need for targeted field and experimental studies to better understand the patterns observed and to improve the modeling of the relationship between SIF and GPP over broad scales.